Global Trends and Opportunities in Hybrid Microgrid Systems Using Renewable Energies - Santos, Daniel de Cerqueira Lima e Penalva; Ihler, Juliana Berendt; Soares, Laene Oliveira; Alves, Yana Amaral; Souza, Cristina Gomez; Boloy, Ronney Arismel Mancebo (International Journal of Energy Economics and Policy, 2022)
Access to energy is related to the essential aspects of modern survival, impacting production processes, access to knowledge and economic development. The global energy demand grows every year, and remote areas without connection to central grids need viable and sustainable alternatives for generating, distributing and storing energy at the local level. This paper presents an analysis through academic research, patent publications, reports and government information to map global trends and identify the opportunities for hybrid systems for power generation in microgrids from renewable sources and with several modes of generation. The data showed recent exponentially rising technologies with a tendency to continue for the next few years. China leads in isolation followed by USA and India. Countries like Brazil and Mexico, despite favourable conditions, do not present local technological development nor are they seen as a market of interest. Technological and research routes point to improving storage processes. Photovoltaic energy source was most used and to lesser extent wind, biomass, bioethanol, biogas, biodiesel and biohydrogen. Most of the inventions were focused on creating and improving machines, equipment, and systems to operate and control, utilizing the Homer software, for example.